Analisis Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) Dalam Pengelolaan Keuangan Di Desa Rejosari Kecamatan Pakis - Dwi Nurrahmawati; Yuanne Gabrila Sriyanto; Nuwun Priyono (Populer: Jurnal Penelitian Mahasiswa, 2023)
The purpose of this research is to find out and describe the effectiveness and efficiency of implementing the siskeudes application as well as the constraints or obstacles to financial management in Rejosari Village, Pakis District. This research uses a qualitative approach with a qualitative descriptive research type. The data used in the study were obtained through interviews and observations at the Rejosari Village Hall office. Data analysis using data reduction, data presentation and verification. The results showed that the implementation of the siskeudes application in Rejosari Village was quite effective and efficient in helping the village government manage its finances. The village financial management procedures that will be carried out include the planning, implementation, management and reporting/accountability stages. However, there are still some problems in its operation but it doesn’t really affect the system used. The village financial system is very important in the village economy, where good and structured village financial management can create optimal accountability and transparency.